Autoimmune disease is associated with a lower risk of progression in monoclonal gammopathy of undetermined significance. (28th December 2020) - Baldursdóttir, Theodóra Rún; Löve, Þorvarður Jón; Gíslason, Gauti Kjartan; Björkholm, Magnus; Mellqvist, Ulf‐Henrik; Lund, Sigrun Helga; Blimark, Cecilie Hveding; Turesson, Ingemar; Hultcrantz, Malin; Landgren, Ola; Kristinsson, Sigurður Yngvi
Abstract: Objectives and methods: We conducted a population‐based study including 19 303 individuals diagnosed with MGUS in Sweden from 1985 to 2013, with the aim to determine whether a prior history of autoimmune disease, a well‐described risk factor for MGUS is a risk factor for progression of MGUS to multiple myeloma (MM) or lymphoproliferative diseases (LPs). Using the nationwide Swedish Patient registry, we identified MGUS cases with versus without an autoimmune disease present at the time of MGUS diagnosis and estimated their risk of progression. Results: A total of 5612 (29.1%) MGUS cases had preceding autoimmune diseases. Using Cox proportional hazards models, we found the risk of progression from MGUS to MM (HR = 0.83, 95% CI 0.73‐0.94) and LPs (HR = 0.84, 95% CI 0.75‐0.94) to be significantly lower in MGUS cases with prior autoimmune disease (compared to MGUS cases without). Conclusions: In this large population‐based study, a history of autoimmune disease was associated with a reduced risk of progression from MGUS to MM/other LPs. Potential underlying reason is that MGUS caused by chronic antigen stimulation is biologically less likely to undergo the genetic events that trigger progression. Our results may have implications in clinical counseling for patients with MGUS and underlying autoimmune disease.